2022
DOI: 10.3390/ma15196521
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan Nanoparticles: A Versatile Platform for Biomedical Applications

Abstract: Chitosan is a biodegradable and biocompatible natural polymer that has been extensively explored in recent decades. The Food and Drug Administration has approved chitosan for wound treatment and nutritional use. Furthermore, chitosan has paved the way for advancements in different biomedical applications including as a nanocarrier and tissue-engineering scaffold. Its antibacterial, antioxidant, and haemostatic properties make it an excellent option for wound dressings. Because of its hydrophilic nature, chitos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(36 citation statements)
references
References 191 publications
(221 reference statements)
1
27
0
Order By: Relevance
“… A high degradation rate which ensures the material’s safety and its protection of the environment (eco-friendly properties) [ 76 ]. Polymers may also be hydrophobic and adhesive; high hydrophobicity prevents blood clotting during circulation [ 77 , 78 ]. …”
Section: Chitosan-based Nanosystem Of Smart Drug Delivery Systemmentioning
confidence: 99%
See 2 more Smart Citations
“… A high degradation rate which ensures the material’s safety and its protection of the environment (eco-friendly properties) [ 76 ]. Polymers may also be hydrophobic and adhesive; high hydrophobicity prevents blood clotting during circulation [ 77 , 78 ]. …”
Section: Chitosan-based Nanosystem Of Smart Drug Delivery Systemmentioning
confidence: 99%
“…Polymers may also be hydrophobic and adhesive; high hydrophobicity prevents blood clotting during circulation [ 77 , 78 ].…”
Section: Chitosan-based Nanosystem Of Smart Drug Delivery Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…There are several important groups of polysaccharides utilized as soft tissue adhesives and hemostatic materials, such as chitin, chitosan, dextran or chondroitin. These materials yield biocompatible and biodegradable adhesives that are composed of natural sugar building blocks that are easy to prepare and apply [21,[42][43][44][45]. A study reported the successful developed of novel biocompatible and degradable biopolymers based on a two-component bio-adhesive system (chitosan and starch).…”
Section: Sources and Types Of Bio-based Adhesivesmentioning
confidence: 99%
“…Chitosan (CS NPs) nanoparticles have several beneficial properties distinguishing them from other nanoparticles, i.e., facility of surface modification, the simple procedure of preparation, high structural stability, excellent solubility, and very good responsiveness to different stimuli [ 8 ]. CS NPs can be obtained using different techniques such as ionotropic gelation, the reverse micellar method, emulsion-droplet coalescence, precipitation, or spray drying [ 13 , 14 , 15 ]. The interest in using chitosan nanoparticles in the delivery of anticancer drugs, results from the properties of chitosan combined with the effect of nanocarriers.…”
Section: Introductionmentioning
confidence: 99%